Peripheral Blood Biomarkers for Early Diagnosis, Severity, and Prognosis of Checkpoint Inhibitor-Related Pneumonitis in Patients With Lung Cancer - Lin, Xinqing; Deng, Haiyi; Yang, Yilin; Wu, Jianhui; Qiu, Guihuan; Li, Suyang; Xie, Xiaohong; Liu, Ming; Xie, Zhanhong; Qin, Yinyin; Song, Yong; Zhou, Chengzhi (Frontiers in Oncology, 2021)
Background Checkpoint inhibitor-related pneumonitis (CIP) is a potentially fatal immune-related adverse event that occurs during treatment with immune checkpoint inhibitors (ICIs). However, the roles played by peripheral blood parameters in CIP development remain unclear. Here, we aimed to identify which blood biomarkers correlated with the development and prognosis of CIP in patients with lung cancer. Methods We conducted a retrospective analysis of 87 patients with CIP (CIP group) and 87 patients without CIP (control group). Cytokines, blood routine, lactate dehydrogenase (LDH) and albumin (ALB) were collected at baseline (before ICIs), at onset of pneumonitis (in the CIP group), and before the last dose of ICI (in the control group). We compared the baseline values and changes over time in various blood parameters between the CIP and control groups. The CIP outcomes were collected and compared according to the median values of these parameters. Results Squamous carcinoma (odds ratio [OR]: 3.02; p = 0.004) and ICI monotherapy (OR: 6.56; p = 0.004) correlated with a high risk of CIP. In the CIP group, interleukin (IL)-6 and platelet-to-lymphocyte ratio (PLR) at CIP were significantly increased relative to baseline. By contrast, IL-6 and PLR reduced over time in the control group. Significant decrease in absolute lymphocyte count (ALC) and increases in IL-10, neutrophil to lymphocyte ratio (NLR), and LDH levels were observed from baseline to CIP. No significant change in these parameters was observed in the control group relative to baseline. ALB decreased in both groups, but the decrease in the CIP group was greater (9.21% vs. 2.44%; p = 0.020). High IL-6 levels (OR: 5.23, 95% confidence interval [CI]: 1.15–23.86; p = 0.033), and low levels of ALB (OR: 0.16, 95% CI: 0.04–0.64; p = 0.009) measured at the time of CIP symptom onset were associated with severe pneumonitis. Low concentration of IL-6 (hazard ratio [HR]: 0.17, 95% CI: 0.03–0.95; p = 0.044) and high ALB levels (HR: 0.28, 95% CI: 0.08–0.94; p = 0.040) were correlated with favorable overall survival in CIP. Conclusions Increase in IL-6, IL-10, NLR, PLR, and LDH levels or reduced ALC and ALB levels were associated with the occurrence of CIP in lung cancer patients. High IL-6 and low ALB levels at onset of CIP were related to severe grade and poor prognosis of CIP.